ANALISIS DINAMIKA POLITIK PENCALONAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH PADA PILKADA SERENTAK 2017 (Studi Kasus Partai Demokrasi Indonesia Perjuangan Kabupaten Pati) - Hermayanti, Ariska Rudy; ., Yuwanto (Journal of Politic and Government Studies, 2018)
Election simultaneously 2017 was a part of democracy at the local level that undertaken directly .To the process the election there are the political dynamics in it , including the dynamics of resulting in a for the candidate .One form of the political dynamics conflict to the process is for the nomination of the head of the provinces and the the head of the region , is no exception PatiRegency; includes a conflict in the main in party that follows haryanto-arifin namely PDI Perjuangan .This research about the dynamics and the election of conflict in the qualitativeresearch methods have technique data collection in the form of interviews and review of documentation .Election simultaneously 2017 of Pati Regency was attended by a single pair of candidates should run smoothly but in fact there are many the political dynamics involving single candidate  haryanto-arifin and  the empty box . The Candidate  Haryanto-Arifin supported by coalition fatconsists of eight party namely PDI Perjuangan, PKB, Golkar, Gerindra, Demokrat, PKS, PPP, and Hanura . Based on calculation KPU of Pati Regency  Haryanto-Arifin win over from empty box by the acquirement of 519.675 sound ( 74,4 % ) , compared to an empty box to 177.762 sound ( 25.6% ).Research has been formulated to analyze the political dynamics that occurs in the next local election simultaneously 2017 of  PDI Perjuangan Pati Regency .The name of a candidate where a number of emergence figures register DPC PDI Perjuangan of Pati Regency , then the process ofcapturing that were organized by DPC PDI Perjuangan of Pati Regency but who have the right to determining requirement is only DPP PDI Perjuangan  .Conflicts between the candidates for when will have no recommendations form the center later merged form volunteers of empty box , namelyconflict single candidates conflict surrounding the  haryanto-arifin against volunteers empty box , political issue money reported to panwas , until idul the determination of official candidates elected by general election commission of Pati Regency then society movement starch submit an application to constitutional court is to undo the award KPU of Pati Regency .Keywords: Democratization, Election, The Political Dynamics